Potret Corporate Social Responsibility (CSR) di Media - Abdul Rohman (Jurnal Komunikasi)
Portray of Corporate Social Responsibility (CSR) on media is no more than complementary part which never appears as main one. Through a descriptive qualitative research, CSR appears on media as part of marketing communication activities communicated by top-level managements. CSR is communicated by buying space on media to gain economical and moral beneficiaries for private companies identified as major sectors that dominantly conduct CSR. Donation considerably becomes major issue in CSR, yet it is a program purposing to empower community and two-ways oriented. Media landscape and its people have significant contribution to CSR’s appearance on media; and, stereotypes existing between both media and CSR initiators affect to the low appearance of CSR on media. Therefore, synergy between both of them is required, either as executor, facilitator, or promoter. By doing so, CSR as one of the efforts to create changes and overcome social problems in Indonesia is possible to be implemented.